2019
DOI: 10.1017/s0022215119000495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors associated with multiple ventilation tube insertions in children with otitis media with effusion

Abstract: ObjectiveTo determine the factors related to multiple ventilation tube insertions in children with otitis media with effusion.MethodsA retrospective review was performed of 126 ears of 81 children aged less than 12 years who had undergone insertion of a Paparella type 1 ventilation tube for the first time between August 2012 and March 2018.ResultsMean age at the first operation was 4.0 ± 2.2 years, and the mean duration of otitis media with effusion before the first ventilation tube insertion was 5.4 ± 4.5 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
1
1
Order By: Relevance
“…In addition, scarring and tympanic membrane retraction are reported to be increased by the several ventilation tube insertions. 15 However, the retraction of the tympanic membrane was not observed in either of the balloon Eustachian tuboplasty and ventilation tube groups in this study. We believe that this is related to the duration of the study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In addition, scarring and tympanic membrane retraction are reported to be increased by the several ventilation tube insertions. 15 However, the retraction of the tympanic membrane was not observed in either of the balloon Eustachian tuboplasty and ventilation tube groups in this study. We believe that this is related to the duration of the study.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the ‘gold standard’ treatment for persistent middle-ear effusion is adenoidectomy, myringotomy and insertion of ventilation tube, some children are refractory to this conventional treatment. 15 Balloon Eustachian tuboplasty with adenoidectomy was performed as a first line treatment modality in our study. Our results demonstrate that although balloon Eustachian tuboplasty was used as the first treatment method, the success of the procedure was high, in accordance with the literature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, studies directly analyzing retention time, performed by Ahn et al and Choi et al, demonstrated that TT retention time was 3.7 months and 2.0 months shorter, respectively, in patients who received repeat insertion. 10,25 Long-term tubes may be particularly beneficial for patients with multiple risk factors for r-TT, although this must be weighed carefully against the associated risks of these tubes including persistent TM perforation or failure to spontaneously extrude. In addition to tube design, tube blockage can also impact the duration of TT function.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for r-TT investigated in our eligible studies included duration of otitis media with effusion (OME) before first TT insertion, 10 family history of ENT problems, 5 history of breastfeeding, 11 history of pacifier use, 11 siblings in the household, 6 neighborhood income level, 4 gastrointestinal disease, 4 antibiotic allergy, 12 and speech difficulties. 12 However, only one study reported data for each of these factors and therefore were not included in our pooled analyses.…”
Section: Risk Factorsmentioning
confidence: 99%